Evolution of rehabilitation services in response to a global pandemic: reflection on opportunities and challenges ahead - Bossuyt, Fransiska M.; Bogdanova, Yelena; Kingsley, Kristine T.; Bergquist, Thomas F.; Kolakowsky-Hayner, Stephanie A.; Omar, Zaliha Binti; Popova, Evguenia S.; Tobita, Mari; Constantinidou, Fofi (Frontiers in Rehabilitation Sciences, 2023)
The rapidly evolving COVID-19 public health emergency has disrupted and challenged traditional healthcare, rehabilitation services, and treatment delivery worldwide. This perspective paper aimed to unite experiences and perspectives from an international group of rehabilitation providers while reflecting on the lessons learned from the challenges and opportunities raised during the COVID-19 pandemic. We discuss the global appreciation for rehabilitation services and changes in access to healthcare, including virtual, home-based rehabilitation, and long-term care rehabilitation. We illustrate lessons learned by highlighting successful rehabilitation approaches from the US, Belgium, and Japan.